Development of an American and Australian co-designed youth mental health literacy program - Grové, Christine; Marinucci, Alexandra; Riebschleger, Joanne (Frontiers in Child and Adolescent Psychiatry, 2023)
Mental health concerns are common in adolescence, with 14% of youths receiving a diagnosis of a mental illness disorder, a figure that is expected to increase post-pandemic. Early intervention is best in childhood, however increased demand after the pandemic coupled with a chronic mental health professional shortage means adolescents are less likely to receive help, leading to potential long-term negative outcomes. An evidence-based mental health literacy school-based program provided an opportunity to share new knowledge about mental health, potentially improving adolescents’ mental health, leading to increased help seeking towards mental health services and help giving. This paper describes a mental health literacy and action program for adolescents, co-designed with several stakeholders including professionals, teachers, parents and adolescence, sharing lessons learned in program development and implementation across two countries, Australia and United States.